Association of physical activity and stress reactivity with depression in elderly hypertensive population: A cross-sectional study from Eastern India - Arijita Banerjee; Sumit Kumar; Shirin Dasgupta (Journal of Family Medicine and Primary Care)
Objective: Depressive disorder poses an increased risk for sudden cardiac death in elderly population with existing comorbidities. Also, few international studies suggest the association of decreased stress reactivity with symptoms of depression in old age. Our cross-sectional study has attempted to explore the relationship of daily exercise and stress reactivity with depression in elderly individuals with hypertension. Methods: Depression was assessed using Hamilton depression rating scale or HAM-D. The physical activity was assessed using the global physical activity questionnaire (GPAQ), developed by WHO. Stress reactivity is calculated from various cardiovascular parameters. The relationship of physical activity and stress reactivity scores on depression was explored using regression analysis. Results: The prevalence rate of depressive symptoms in elderly hypertension population was around 40.2%. Significantly lower reactivity scores (P = 0.032) to deep breathing were evident in elderly hypertension population. After proper adjustment of the confounding factors, regression analysis depicted that decreased physical activity (Odds ratio = 4.48; 95% Confidence interval = 2.32–7.69) resulted in heavy risk of developing depressive symptoms besides old age and low educational status. Conclusion: Our ﬁndings suggest that low physical activity leads to the development of depressive symptoms and decreased stress reactivity among elderly hypertensive patients.